Historiography of contemporary economics - Eliot Roy Weintraub; Till Düppe (Duke University, Center for the History of Political Economy (CHOPE), 2018)
This paper is a concatenation of the penultimate versions of the first and last chapters of the book A Historiography of Contemporary Economics, edited by Düppe and Weintraub, to be published by Routledge Press in late 2018. The volume itself collects commissioned essays on recently developed modes and strategies for writing the history of economics.
Keywords: A33; B2; B3; B4; 330; historiography; oral history; social media; prosopography; network analysis; textbooks; artifacts; popular economics; witness seminars; economics syllabi; economics examinations